A mechanistic model for the nonlinear bond behavior of steel reinforcement in concrete. (15th March 2021) - Huang, Le; Ye, Hailong; Xu, Lihua; Chi, Yin
Highlights: A new mechanistic model is proposed to simulate the nonlinear bond behavior. The experimentally observed characteristics of the bond behavior are appropriately embodied. The underlying mechanisms responsible for the nonlinearity are exhibited in a numerical manner. Abstract: In this work, a new mechanistic interface model is proposed to simulate the nonlinear bond behavior of steel reinforcement in concrete. With the motivations to reproduce the bond response more realistically and uncover the underlying mechanisms responsible for the high nonlinearity, the main characteristics including the damage evolution and frictional features are properly embodied during the establishment of the model. Specifically, the collective bond stress is expressed as the superposition of the mechanical interlocking and the frictional resistance, while the total reinforcement slip is first decomposed into three components, namely elastic slip, plastic slip, and sliding slip. As to the interfacial damage, by introducing a probabilistic method and the concept of cumulative slip, the irreversibility and directionality are emphatically considered. Upon these assumptions, along with mathematical and physical laws governing the developments of interfacial damage, kinematic/isotropic hardenings, and frictional sliding, the model is strictly deduced and numerically implemented within the thermodynamic framework. The numerical illustrations of the model behavior under different loading paths and the independent validations with different test results demonstrated that the proposed model is capable of reproducing the bond responses satisfactorily. The nonlinearity of the bond behavior is the integrative result of the variations of interlocking force and frictional resistance, which is largely attributed to the progressive transformation of the dominated mechanisms at different debonding stages. The presented model constitutes a beneficial addition to the understanding of the nonlinear bond behavior from the theoretical viewpoint.